Theoretical architecture design of a community risk prevention big data platform - Jia, N.; Guo, D.; Y. Chen; Y. Liu (Qinghua Daxue Xuebao/Journal of Tsinghua UniversityQinghua Daxue Xuebao/Journal of Tsinghua UniversityQinghua Daxue Xuebao/Journal of Tsinghua University, 2019)
Since communities are the basic units for public safety management, community risk prevention is of great significance. Community risk prevention must first identify community risks for people, things and management. This study analyzed the characteristics and causes of community risk to identify community risk prevention methods and how to monitor, control, predict, quickly detect and prevent community risk. Current international development trends for community risk prevention are reviewed to show that big data platforms are the key technology for community risk prevention. Finally, this paper describes the function, structure and construction of a large data platform for community risk prevention. This research on community risk prevention and big data platforms provides theoretical and technical support for community safety and security. © 2019, Tsinghua University Press. All right reserved.
Keywords: Architecture designs; big data; Community risk; Community safety; Data platform; International development; Key technologies; Large data; Large data platform; Risk management; Risk prevention; Safety engineering; Technical support; Theoretical architecture design